CNS Infections A Clinical Approach (Springer International Publishing, 2018)
This updated and expanded second edition covers selected infections of the central nervous system of considerable current interest. Aspects that are less well documented, such as spinal cord infections, central nervous system infections in patients with cancer, tropical infections, healthcare-associated ventriculitis or meningitis, and immunological problems in the international traveler are also discussed, as these are all problems relevant to daily practice. It is a multi-authored book written by experts in the field of neurological infection. A new section on infectious neuropathies is included. CNS Infections: A Clinical Approach is of value to the busy clinician; the neurological international community as well as all primary care doctors, internal medicine specialists and residents who take care of patients with suspected neurological infections.